Mean-drawdown risk behavior: drawdown risk and capital asset pricing - Baghdadabad, Mohammad Reza Tavakoli; Nor, Fauzias Mat; Ibrahim, Izani (Journal of Business Economics and Management, 2013)
We develop an alternative approach based on mean-drawdown risk behavior versus the mean-variance behavior. We develop two risk measures as the maximum draw down risk and average drawdown risk to estimate two new betas and then propose two CAPM-like models. The data includes a comprehensive universe of more than 11,000 US equity-based mutual funds from first month of 2000 to third month of 2011.The evidence clearly shows superiority of the maximum and average drawdown betas and their pricing models, the maximum drawdown CAPM and the average drawdown CAPM, over the traditional beta and CAPM, respectively.